Mikroplastik sebagai Kontaminan Anyar dan Efek Toksiknya terhadap Kesehatan - Supit, Alva; Tompodung, Linda; Kumaat, Sicilia (Poltekkes Kemenkes Tanjung Karang, 2022)
Microplastics are synthetic polymers that are unable to be completely degraded and will stay as an environmental contaminant for a long period of time. Due to their microscopic size, microplastics are able to enter the human body, either directly or indirectly via the food chain, where both processes will induce pathological changes in-vivo. So far, clinically, there has been no direct evidence yet about any microplastic-related disease in humans. However, since Indonesia is a maritime country and has been producing microplastics on a large scale, it is critical for our healthcare personnel to have the knowledge about microplastic toxicokinetics and the possible pathological responses elicited by humans when exposed to microplastics. This review article aims to discuss the definition, genesis, accumulation process, toxicokinetics, and pathological responses due to microplastic exposure, emphasizing the biomolecular aspects and implying the possible effects on public health. An internet search in Google Scholar and Pubmed was performed using keywords